1989
DOI: 10.1346/ccmn.1989.0370104
|View full text |Cite
|
Sign up to set email alerts
|

Weathering of Iron-Bearing Minerals in Soils and Saprolite on the North Carolina Blue Ridge Front: II. Clay Mineralogy

Abstract: Abstract--The mineralogy of the clay fraction was studied for soils and saprolite on two Blue Ridge Front mountain slopes. The clay fraction contained the weathering products of primary minerals in the mica gneiss and schist parent rocks. Gibbsite is most abundant in the saprolite and residual soil horizons, where only chemical weathering has been operable. In colluvial soil horizons, where both physical and chemical weathering have occurred, the clay fraction consists largely of comminuted primary phyllosilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 30 publications
0
8
0
2
Order By: Relevance
“…The apparent resistance of chlorite to chemical weathering allows its comminution even into the clay fraction (Graham et al, 1989). The persistence of primary chlorite throughout soil profiles was observed by Bain (1977) in weakly developed till-derived soils in Scotland.…”
Section: Chloritementioning
confidence: 93%
“…The apparent resistance of chlorite to chemical weathering allows its comminution even into the clay fraction (Graham et al, 1989). The persistence of primary chlorite throughout soil profiles was observed by Bain (1977) in weakly developed till-derived soils in Scotland.…”
Section: Chloritementioning
confidence: 93%
“…The origin of the trioctahedral variety of vermiculite remains unclear (Justo et al, 1986;de la Calle and Suquet, 1988;Zhelyaskova-Panayotova et al, 1992 whereas the dioctahedral variety is unquestionably accepted as the product of low-temperature surface weathering (Gruner, 1939;Hathaway, 1955;Barshad and Kishk, 1969;April et al, 1986;Graham et al, 1989;Moon et al, 1994). Experimental studies produced vermiculite as an alteration product of micas Toksoy-Krksal, Ttirkmeno~lu, and GOnciao~lu Clays and Clay Minerals owing to the effects of low-alkali solutions (Komarneni and Roy, 1981).…”
Section: Inductively Coupled Plasma Spectrometry Analysismentioning
confidence: 99%
“…Chemical weathering of chlorites in soils may result in its complete destruction or in its transformation to vermiculite, smectite or related interstratified minerals (Ryan et al, 2008). However, some studies showed that chlorite was resistant to chemical alteration through the soil, which allowed its comminution into the clay fraction (Graham et al, 1989). Based on the results obtained, we presume faster chlorite destruction in profile 1 with the lowest pH values (less soil clay minerals) and more pronounced transformation of chlorite to other mineral phases in profiles 2 and 3 (more soil clay minerals).…”
Section: Bulk and Clay Mineralogymentioning
confidence: 99%